The Effect of Gender Equality and Job Stress on Turnover Intention with Job Satisfaction as Mediator - Estrella Estrella; Ahmad Salahuddin; Hasanudin Hasanudin; Ikram Yakin (Komunitas Dosen Indonesia, 2025)
The retail industry faces significant challenges in terms of employee turnover, particularly at Indomaret. The main objective of this study is to examine the potential impact of gender equality and job stress on turnover intention employee Indomaret, both directly and through mediation by job satisfaction. A high employee turnover rate is a sign of problems in management. Data were collected through a questionnaire distributed via Google Forms, with 120 respondents. Structural Equation Modeling (SEM) and Partial Least Squares (PLS) were used as data measurement methods, utilizing the SmartPLS 3 application. The research analysis findings were determined at a significance level of 0.05, indicating that gender equality negatively impacts turnover intention but positively affects job satisfaction. On the other hand, job stress significantly affects turnover intention and decreases employee job satisfaction. Additionally, gender equality and job stress significantly impact turnover intention, mediated by job satisfaction. This research is expected to contribute by providing information, additional insights, and better literature related to factors that can influence the Indomaret company in Pontianak City and practical implications for human resource management. Additionally, expected to serve as a consideration for the company to take steps to improve job satisfaction and reduce turnover intention.